Dental caries’ experience, prevalence and severity in mexican adolescents (2009)
Objective Determining dental caries’ experience, prevalence and severity in students applying for degree courses at San Luis Potosi University (UASLP). Material and Methods A cross-sectional study was carried out involving adolescents and young adults (16 to 25 years old) applying for undergraduate courses at UASLP (~10 %, n=1 027). Two standardized examiners undertook dental examinations; DMFT index, prevalence (DMFT and gt;0), severity (DMFT and gt;3 and DMFT and gt;6) and significant caries index (SiC) were calculated. STATA 9.0 non-parametric tests were used for statistical analysis.Results Mean age was 18.20±1.65; 48.0% were female. The DMFT index was 4.04±3.90 and caries prevalence was 74.4%. Regarding caries’ severity, 48.8% had MDFT and gt;3 and 24% DMFT and gt;6. The SiC index was 8.64. Females had higher caries experience than males (4.32±4.01 cf 3.78±3.78; p0.05). Age was associated with both experience (p